Network intrusion analysis methodologies, tools, and techniques for incident analysis and response - Fichera, Joe, 1966-; Bolt, Steven (Elsevier, 2013)
Network Intrusion Analysis teaches the reader about the various tools and techniques to use during a network intrusion investigation. The book focuses on the methodology of an attack as well as the investigative methodology, challenges, and concerns. This is the first book that provides such a thorough analysis of network intrusion investigation and response.